Synchronization of Protected Rice Field (LSD) Data with PPAT Deeds: Administrative Constraints in Urban Land Rights Transfer - Muhammad Ali; Nurhayati Nurhayati (Jurnal Smart Hukum (JSH), 2026)
This article examines the administrative constraints arising from the lack of synchronization between data on Protected Rice Fields (Lahan Sawah yang Dilindungi, LSD) and the deeds of sale and purchase (Akta Jual Beli) drawn up by Land Deed Officials (PPAT) in urban areas in Indonesia. Empirically, problems emerge when land has been transferred and registered at the Land Office, but later the urban planning office refuses to issue building permits because the plot is categorized as agricultural land or green zone under LSD mapping. This situation generates legal uncertainty regarding the object of sale and purchase, burdens bona fide buyers, and creates potential conflicts between spatial planning law, agricultural land protection, and land registration administration. Using a qualitative normative‑empirical method, this research analyzes the regulatory framework on LSD, sustainable food crops farmland protection, and the role of PPAT and the Land Office, combined with case‑based analysis from urban contexts. The study argues that the current regime does not sufficiently ensure legal protection and certainty for purchasers of land already bearing registered rights but subsequently designated as LSD in spatial and sectoral maps. It concludes that systematic synchronization of LSD data into land registration and PPAT due‑diligence procedures, as well as a policy of review and reclassification of urban agricultural plots, is required to restore legal certainty and balance between food security objectives and urban development needs.